Guidance Note on Information Sharing Between IMF and World Bank Staff. (Policy Papers; Policy Paper ;, 2022)
This Guidance Note outlines good practices on information-sharing across key areas in which the Bank and the IMF interact. The note outlines general principles consistent with these frameworks and discusses how the staffs of the two institutions are expected to exchange information related to country operations, technical assistance, and policy work.